Plasma glial cell line-derived neurotrophic factor in patients with major depressive disorder: a preliminary study. Issue 1 (30th June 2015) - Lee, Bun-Hee; Hong, Jin-Pyo; Hwang, Jung-A; Na, Kyoung-Sae; Kim, Won-Joong; Trigo, Jose; Kim, Yong-Ku
Abstract : Background: Some clinical studies have reported reduced peripheral glial cell line-derived neurotrophic factor (GDNF) level in elderly patients with major depressive disorder (MDD). We verified whether a reduction in plasma GDNF level was associated with MDD. Method: Plasma GDNF level was measured in 23 healthy control subjects and 23 MDD patients before and after 6 weeks of treatment. Results: Plasma GDNF level in MDD patients at baseline did not differ from that in healthy controls. Plasma GDNF in MDD patients did not differ significantly from baseline to the end of treatment. GDNF level was significantly lower in recurrent-episode MDD patients than in first-episode patients before and after treatment. Conclusions: Our findings revealed significantly lower plasma GDNF level in recurrent-episode MDD patients, although plasma GDNF levels in MDD patients and healthy controls did not differ significantly. The discrepancy between our study and previous studies might arise from differences in the recurrence of depression or the ages of the MDD patients.